How do filter types of renal replacement therapy affect survival in critically ill patients? Concerns about adsorption of nafamostat mesylate on AN69 membranes - Yiqi Qian; Wei Wu; Minmin Wang; Yifan Wei; Ming Zhong (BMC Nephrology, 2024)
Abstract We are writing to you in response to the article published in BMC Nephrology titled “Dose of nafamostat mesylate during continuous kidney replacement therapy in critically ill patients: a two-centre observational study”. The study provided valuable information on the use of nafamostat mesylate (NM) during continuous renal replacement therapy (CRRT) in critically ill patients. We noticed in this study that a higher dose of NM resulted in a decrease in ICU and hospital mortality. However, the underlying mechanism behind this phenomenon remains unclear. We believe exploring this further is warranted.